Low Survivals and Rapid Demographic Decline of a Threatened Estuarine Delphinid - Lin, Wenzhi; Zheng, Ruiqiang; Liu, Binshuai; Chen, Shenglan; Lin, Mingli; Liu, Mingming; Liu, Wenhua; Li, Songhai (Frontiers in Marine Science, 2022)
Beibu Gulf’s Indo-Pacific humpback dolphins (BBG) present both genetic differentiation and phenotypical difference from conspecifics from other areas of the South China Sea. Given the recent urbanization and industrialization in southern China, humpback dolphins from the BBG warrant conservation attention. However, this population’s demographic trend is unclear, making it hard to take conservation measures. To assess the population status of humpback dolphins in the BBG, photo-identification surveys were conducted since 2015 in the inshore region surrounding the Dafeng River Estuary, which represents the most urbanized and industrialized coastal area of the BBG region. Robust design modeling resulted in low estimated survival ranging between 0.854-0.923. Correspondingly, the annual abundance of population experienced a steady decline from 141 (95% CI: 117-169) in 2015 to 102 (95% CI: 92-114) in 2019. The estimated survival exhibited different variations depending on the animals’ age and sex categories. Unexpectedly, the dolphin survival increased in 2017-2018 for unknown reasons, slowing down the population decline in the last two survey years. We showed that dolphin survival in stressful environments may vary substantially between different sex and age groups. In a broader perspective, high-resolution data is crucial to examine the age/sex-structured demographic dynamics of threatened dolphins, which could be further used for a more accurate extinction risk assessment and a strategic conservation action.